PERAN KOMUNIKASI INTERPERSONAL ORANG TUA PADA KINERJA BELAJAR ANAK SEKOLAH DASAR DALAM PENDAMPINGAN PJJ PADA MASA PANDEMI COVID-19 DI SD NEGERI TANJUNG BARAT 09 KOTA JAKARTA SELATAN - Jihan Tsurayya, (2022)
This study aims to determine the role of parental interpersonal communication on the learning performance of elementary school children in Distance Learning Assistance (PJJ) during the COVID-19 pandemic at SD Negeri Tanjung Barat 09, South Jakarta City. The researcher uses this type of qualitative research with a descriptive approach. The data collection technique used in-depth interviews with five pairs of informants. The data analysis technique used by the researcher is the Miles and Huberman analysis technique which consists of three stages, namely data reduction, data display, and drawing conclusions. The theory used by researchers in this study is the theory of symbolic interaction. The final result of this study shows that the role of interpersonal communication carried out by parents to elementary school children on children's learning performance during PJJ mentoring is very effective as evidenced by the effects and positive changes on children's self and behavior. The changes seen in children are that they become closer and comfortable to tell parents about their complaints in learning so that parents can provide solutions and motivation, so of course children's learning performance can increase both in terms of quality, quantity and time. This situation is different from before the implementation of the PJJ because before the implementation of the PJJ they did not have much time with their parents so they had low intensity and communication between parents and children was very rare. Broadly speaking, the role of parental communication in Distance Learning (PJJ) assistance during the COVID-19 pandemic is very effective on the current learning performance of elementary school children as evidenced by the positive effects and changes on themselves and the behavior of elementary school age children.